Different Pattern of Cardiovascular Impairment in Methylmalonic Acidaemia Subtypes - Liu, Ying; Yang, Ling; Shuai, Ruixue; Huang, Suqiu; Zhang, Bingyao; Han, Lianshu; Sun, Kun; Wu, Yurong (Frontiers in Pediatrics, 2022)
Methylmalonic acidaemia (MMA) has been reported to be associated with cardiovascular involvement, especially for the combined type with homocystinuria. We have screened 80 control subjects and 99 MMA patients (23 isolated type and 76 combined type) using electrocardiograph and echocardiography. 32 cases (34%) of ECG changes were found including sinus tachycardia (n=11), prolonged QTc interval (n=1), I-degree atrioventricular block (n=1), left axis deviation (n=5) and T wave change (n=14). By echocardiography, 8 cases of congenital heart disease were found in 4 combined MMA patients (5.3%) including ventricular septal defect (n=2), atrial septal defect (n=3), patent ductus arteriosus (n=1) and coronary artery-pulmonary artery fistula (n=2). Pulmonary hypertension (n=2) and hypertrophic cardiomyopathy (n=1) in combined subtype were also noted. Moreover, echocardiographic parameters were analysed by multiple regression to clarify the influence of different subtypes on cardiac function. It was found that the left ventricular mass index (LVMI) was significantly reduced only in combined subtype (R= -3.0, 95%CI (-5.4, -0.5), P = 0.017). For left ventricle, the mitral E' velocity was significantly reduced (isolated type: R= -1.8, 95%CI (-3.3, -0.4), P=0.016; combined type: R= -2.5, 95%CI (-3.5, -1.5), P<0.001), the global longitudinal strain (GLS) was the same (isolated type: R= -1.4, 95%CI (-2.3, -0.4), P=0.007; Combined type: R= -1.1, 95%CI (-1.8, -0.4), P=0.001), suggesting weakened left ventricular diastolic and systolic functions in both subtypes. For right ventricle, only in combined subtype, the tricuspid E' velocity was significantly reduced (R= -1.4, 95%CI (-2.6, -0.2), P=0.021), and the tricuspid annular plane systolic excursion (TAPSE) was the same (R= -1.3, 95%CI (-2.3, -0.3), P=0.013), suggesting impaired right ventricular systolic and diastolic function. In conclusion, isolated and combined types showed different pattern of cardiac dysfunction, specifically the former only affected the left ventricle while the latter affected both ventricles. And it is necessary to perform echocardiographic screening and follow up in both MMA subtypes.